Stability of Î² -carotene in Sterilized Flavoured Milk - Ramasamy, D; Manoharan, A; Sudha, K; Prabakaran, C (Indian Journal of Dairy Science, 2012)
An attempt has been made to standardize the preparation of sterilized flavoured milk satisfying the daily recommended intake of Î²-carotene. Flavoured milk enriched with 5, 7.5, 10 and 12.5% levels of carrot juice with 0.1% cardamom and 10% sugar was studied for their sensory acceptance. The expert panel rejected the 12.5% enrichment which had lowest sensory acceptance. The accepted levels of enrichment (5, 7.5 and 10% levels) were further studied for the Î²-carotene content and stability of ?-carotene for a period of 3 months under light and dark storage conditions. Results of the study indicated that only negligible loss of Î²-carotene was observed during this period in all three enrichment levels. Sterilized flavoured milk enriched with 5%, 7.5% and 10% carrot juice of 200ml servings were found suitable for satisfying the RDA for Î²-carotene to children, adult men/women and pregnant woman respectively.